THE USE OF THE PHONICS METHOD IN THE LITERACY PROCESS OF 1ST GRADE ELEMENTARY SCHOOL STUDENTS: AN EXPERIENCE REPORT - de Lourdes Andrade Jovial Macarini, Sandra (Revista Gênero e Interdisciplinaridade, 2026)
The present experience report aims to describe the application of the phonics method in a 1st-grade class of Elementary School, highlighting the pedagogical strategies used and the results observed in the literacy process. The activities involved the development of phonological awareness, the recognition of letter sounds, the association between phonemes and graphemes, educational games, reading and writing of simple words and sentences. The results showed progress in the identification of speech sounds, word reading, and students’ interest in literacy activities. It is concluded that the phonics method, when applied systematically and contextually, contributes significantly to the initial learning of reading and writing.